Climate change of another kind - Bhaduri Amit (Economic& Political weekly, 2013)
Changes in the climate of economic policy affect more directly and immediately our everyday life compared to changes in the global physical climate. And, yet, while physical climate change receives a good deal of attention and research, economic climate change is seldom noticed and rarely commented upon. The sustained attack on Keynesian demand management in the name of sound finance has re-established the dominance of finance capital the world over, except in a few latin American countries where social democracy has forced it way into policy in a new guise. Indias subservience to Washington and to global finance is shameful because even as its economy has done well on the growth front, the people have not.
Keywords: Climate change